Simultaneous and rapid colorimetric detection of distinct miRNAs using Split-LAMP - Chua, Yi Jing; Sim, Steven Poh Chuen; Shridharan, Medha; Seow, Yiqi (Frontiers in Bioengineering and Biotechnology, 2023)
Aberrant microRNA (miRNA) expressions are often discovered in many life-threatening diseases such as cancer. In particular, recent studies show combinations of miRNA levels have greater diagnostic accuracy as opposed to single miRNA levels. For point-of-care applications, rapid and sensitive isothermal amplification with loop-mediated isothermal amplification (LAMP) has gained significant interest. We aimed to develop a cost-effective point of care testing (POCT) device for multiple miRNAs that can integrate miRNA signals into a single output. We demonstrate that the loop primers for LAMP can be broken and be used for miRNA detection. This split-LAMP approach provides a logic AND-gate output for two distinct miRNA inputs. We then show that this is potentially usable in point-of-care testing using pH-sensitive dye to give a rapid, colorimetric endpoint readout within 30 minutes. This novel logic gate approach can potentially be extended to multiple miRNAs such that there can be a powerful diagnostic concept for multiple short RNAs in a point-of-care rapid test.